Umbilical burns in neonates following traditional cord practices: A case series - Ankit Mishra; Joanne Atkins; Isabel Jones (Elsevier, 2022)
Many cultures have developed traditional practices around the management of the umbilical cord stump in the newborn. Treatment with hot water compress or fomentation is well-documented in sub-Saharan Africa but can result in thermal injuries in vulnerable neonatal skin. We report three cases of superficial partial thickness umbilical burns in infants following such treatment that presented to a paediatric burns unit in London, UK in 2020, all from a Nigerian background. In each case, the burn wound healed with conservative management only. This is a previously unreported cause of neonatal burn injury and we aim to raise awareness of the risks that traditional cord practices may pose to the newborn.